2020
DOI: 10.1108/ci-02-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Moderating claims and disputes through collaborative procurement

Abstract: Purpose Following the global financial crisis in 2008, the construction sector in UAE has been facing emergent criticisms for growing adversarial culture and rising prevalent claims and disputes between stakeholders. The complex, large size and fast track nature of construction projects in UAE, make project management very challenging under the commonly used traditional procurement routes. This paper aims to examine whether implementing collaborative procurement approaches can facilitate resolving the escalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The findings of Table 1 have highlighted the selection of the most suitable procurement method and on the other hand, several authors recognised the collaborative/partnering approach itself as a method of dispute avoidance. The strategies such as team building, improved relationships and communication are also identified as dispute avoidance strategies by the authors which are the special characteristics of the collaborative approach as identified by Elhag et al (2020). Moreover, the early involvement of the contractor is also identified as a dispute avoidance strategy where the focus again moves towards procurement methods because in management oriented, design and build, and collaborative methods early contractor involvement is clearly visible as per Table 2.…”
Section: Dispute Avoidance Strategiesmentioning
confidence: 92%
See 3 more Smart Citations
“…The findings of Table 1 have highlighted the selection of the most suitable procurement method and on the other hand, several authors recognised the collaborative/partnering approach itself as a method of dispute avoidance. The strategies such as team building, improved relationships and communication are also identified as dispute avoidance strategies by the authors which are the special characteristics of the collaborative approach as identified by Elhag et al (2020). Moreover, the early involvement of the contractor is also identified as a dispute avoidance strategy where the focus again moves towards procurement methods because in management oriented, design and build, and collaborative methods early contractor involvement is clearly visible as per Table 2.…”
Section: Dispute Avoidance Strategiesmentioning
confidence: 92%
“…Moreover, Naoum and Egbu (2016), stated that alternative procurement methods like design and build, management contracting and construction project management are introduced to overcome the problems from lack of integration, separation of design from construction, improper communication, uncertainty, changes in environment and client's expectations. Furthermore, Elhag et al (2020) emphasised the use of collaborative approach due to its benefits as improved relationships and communication, better productivity and decrease of disputes and litigation. Moreover, change in attitudes and emphasis on trust are the guiding factors of dispute prevention scheme in collaborative method (Mante et al, 2012).…”
Section: Procurement Methods In the Construction Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in research at the level of firm behaviour, a survey of the definition and classification of off-site construction methods (Ayinla et al, 2019), the role of innovation brokers (Sergeeva and Liu, 2019) and the role and evaluation of iContract, an intelligent contracting technology (McNamara and Sepasgozar, 2020), a review of the use of VR to facilitate communication (Wen and Gheisari, 2020), technology management systems and practical guidance for physical-mechanical robotic systems (Linner et al, 2020), building information modelling (BIM), a review of public client initiatives on demonstrations (Lindblad and Gustavsson, 2021). And, in-depth research based on questionnaires and interviews with experts has been conducted, on real-world and impact studies on loosely coupled systems in construction (Sandberg et al, 2020), theories and case studies on the contribution of tact production to construction production flow (Lehtovaara et al, 2021), on lean procurement readiness (Suresh and Arun Ram Nathan, 2020), a discussion on barriers to adoption of building information modelling in small and medium-sized enterprises (SMEs) (Saka and Chan, 2020), an examination of lean building surveying services from a waste reduction perspective (Khan (Khan and Ali, 2020) and a study on collaborative procurement methods to mitigate claims and disputes (Elhag et al, 2020). Although we have surveyed these recent innovation-related studies to some extent as comprehensively as possible, there are not many studies that properly integrate and structure semi-macro, micro and expert-level research.…”
Section: Recent Prior Researchmentioning
confidence: 99%